Pengaruh Penggunaan Media Sosial terhadap Interaksi Sosial di Kalangan Mahasiswa Universitas Terbuka UPBJJ Yogyakarta - Triya Ameliya; Epsi Euriga (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to examine the use of social media and its impact on social interactions among students at the Universitas Terbuka UPBJJ Yogyakarta, as well as to identify the positive and negative effects of social media usage on these interactions. With the rapid development of technology, social media has become a primary platform for individuals to communicate, share information, and build social connections. This qualitative research utilizes a descriptive approach, conducted through interviews on Saturday, November 23, 2024, with five students from the 7th semester of the Communication Studies Program at Universitas Terbuka, selected using purposive sampling. The findings show that the most frequently used social media platform among students is Instagram, primarily for sharing visual content related to personal and academic activities. Additionally, Facebook and WhatsApp are also used as communication tools for social and academic purposes. The use of social media has positive effects, such as facilitating the expansion of social networks, accelerating the dissemination of information, and enhancing academic experiences. However, excessive use of social media can lead to negative effects, including addiction, social isolation, and a decline in face-to-face interactions. Therefore, it is recommended that students use social media wisely to maximize its benefits without diminishing the quality of direct social relationships.